Using art for older persons with dementia / Akehsan Dahlan, Syamsul Anwar Sultan Ibrahim and Nur Atiqah Azman - Dahlan, Akehsan; Sultan Ibrahim, Syamsul Anwar; Azman, Nur Atiqah (2023)
Ageing is a phenomenon experienced by every country in the world. It is projected that 1 in 6 people in the world will be 60 years and over with 1.4 billion older populations by 2030. Malaysia is no exception with expected 15% older adult population in 2030. The growth of older populations, from 3.5 million (10.7%) in 2021 to 3.6 million (11.1%) in 2022 (as in Figure 1) indicated the increased life expectancy of the baby boomer’s generation, from 63.6 years (2011) to 75.6 years in 2021. Malaysia provides the best treatment for their older adult population. Although older populations are mostly affected with bad health conditions, Malaysia holds its promise to prepare for super ageing nation so the elders can live with comfort and dignity through provision of better healthcare services. The country aims to prepare the older adults to be healthy, independent and live a quality life, physically, psychologically and socially.